China: A Lesson to Learn - Randhawa, Gurpreet (Indian Journal of Marketing, 2004)
India and China have become the countries of strategic importance in the world. Both countries are the favourite destinations for foreign investors. India and China offer a vast market for MNCs.In addition, cheap labour of these countries attracts MNCs for lower cost of production. Both compete with each other to attract the foreign investors by one way or other, as both posses almost similar geographical and economic conditions.